Enhancing physics students' computational thinking and self-regulation using team-based flipped instruction - Astilla, John Carlo S.; Monterola, Sheryl Lyn C.; Taduran, Regina Carla R.; Que, Elenita N. (Quezon City College of Education, University of the Philippines Diliman, 2019)
This study aimed to analyze whether computational thinking and self-regulation of the students who learned using Team-Based Flipped Instruction (TBFI) were netter than students who learned using Conventional Instruction (CI). It also determined if self regulation is a positive predictor of computational thinking in Physics. Two group pretest-posttest quasi-experimental design was utilized in this study. Two intact classes consisting of 130 grade 10 students enrolled in public high school in San Mateo, Rizal in the S.Y. 2018-2019 where randomly assigned to either experimental (TBFI) and conventional group (CI). TBFI has two parts namely out-of-class preparation (OCP) and in-class activities (ICA) wherein ICA has three subparts namely, (a) readiness assurance test (RAT), (b) application activities (AA), (c) Assessment. On the other hand, CI used the usual lecture-discussion, group work lab activity/worksheet, homework and open-ended questions. Two instruments were used to assess the students' computational thinking (CT) and self regulation. The Physics Computational Thinking Test (PCTT) and Self-Regulation Strategy Inventory - Self Report (SRSI-SR). PCTT is a 5-item problem solving test which was composed pf four subquestions namely: decomposition, pattern recognition, abstraction, and algorithm. It is a researcher made test which was validated by experts and pilot tested among Grade 11 students in the San Mateo and Rodriguez, Rizal with similar characteristics of the research sample. While SRSI-SR was adopted with permission from Cleary (2006). The data were analyzed by analysis of covariance (ANCOVA) with independent samples t-test for effectivity of the instruction and simple linear regression to determine the relationship between the variables. Results showed that students exposed to TBFI significantly improved their computational thinking than CI students while self-regulation did not show a significant difference. Moreover, a delayed posttest of two months after the intervention was conducted and the data revealed a significant improvement in computation thinking and self-regulation. The components of these variables were also presented in this study to show specific effects on the computational thinking and self-regulation of the results. Lastly, self-regulation is a significant positive predictor of computational thinking. Quantitative data using students' learning journal, online group discussion via FB group and voice record of the students during ICA were used to support and strengthen the result of this study. Additionally, this study poses significance among science educators, administrators, curriculum developers/planners, instructional developers, teacher education institution, and researchers.
Thesis (Master of Arts in Education - Physics Education)--University of the Philippines, Diliman
Includes bibliographical references (pages 149-163).
Keywords: Physics -- Study and teaching (Secondary) -- Philippines -- San Mateo (Rizal).; Physics -- Study and teaching (Secondary) -- Philippines -- Rodriguez (Rizal).; Critical thinking; Team-Based Flipped Instruction; Physics Computational Thinking Test; Self-Regulation Strategy Inventory-Self Report